Long-term Clinical Outcomes After Syndesmosis Fixation With K-wires in Ankle Fractures With Syndesmotic Instability - Diogo Vieira Cardoso MD; Filippo Pierobon MD; Anne Lübbeke-Wolff DSc; Victor Dubois-Ferrière MD (Foot & Ankle Orthopaedics)
Background: Syndesmotic instability is a significant concern in the management of unstable ankle fractures, occurring in approximately 10% to 13% of these cases. Early recognition and stabilization of syndesmotic injuries are essential to ensure optimal long-term outcomes. Several techniques are currently in use, often involving complex procedure and/or costly devices. Our study presents a syndesmosis fixation technique using K-wires that is both simple and cost-effective. Methods: This is a retrospective single-center case series. Three hundred seventy-seven ankle fractures with intraoperative syndesmosis instability and subsequent syndesmosis fixation with a K-wire were treated between 2002 and 2012. Of the 377 patients, 51 died and we were able to obtain long-term questionnaire completions from 94 patients (29% of presumed living patients), with a mean follow-up of 10.6 ± 3.0 years. Results: The mean age was 46.6 ± 18.5 years; 42% were Danis-Weber type B and 58% type C fractures. Syndesmosis fixation failure was observed in 9 (2%) patients, and 5 (1%) patients had K-wire displacement without loss of syndesmosis reduction. The Manchester-Oxford Foot Questionnaire (MOXFQ) was obtained 10±3 years after surgery. The mean MOXFQ pain score was 25.9 ± 25.4, the mean functional score was 18 ± 24.8, and the mean social score was 13.7 ± 22.2. Conclusion: We report long-term (10.6 ± 3 years) functional outcomes using a validated patient-reported questionnaire in patients who underwent syndesmosis fixation with 2 K-wires for unstable ankle fractures. In the subset of patients we were able to find in follow-up, we found low rates of syndesmosis fixation failure, low pain scores, and excellent functional outcomes. The availability and low cost of these implants make this technique an accessible and cost-effective solution to consider for syndesmosis fixation. Level of Evidence: Level IV, retrospective case series.